Criza COVID-19: provocări pentru piața muncii din România - Ilie, Simona (Calitatea Vieții, 2020)
The paper draws attention to the impact of the COVID-19 context on the labor market. Based on the secondary data analysis, a classification of the economic branches regarding the risk of affecting the activity is sketched. The higher risk tends to complement other employment vulnerabilities (lower wage level, higher share of selfemployment). The Romanian protective measures of employment and incomes fit the European practices of the current context. However, there is a risk of not being able to respond adequately to the increase of poverty and inequality.